Control of Hybrid Distributed Energy Resources with Storage Connected to Microgrid - Ferdous M.M. (IOP Publishing Ltd, 2023)
Renewable energy based distributed generators (DGs) assume an overwhelming role in electricity creation, with the expansion in global warming. Distributed generation dependent on wind, solar energy, diesel generator the utilization of energy units and battery energy storage will give significant force in the near future. Advantages like environmental friendliness, expandability, and adaptability have made distributed generation, controlled by different renewable and nonconventional micro-sources, an attractive alternative for designing current electrical system. A microgrid consists of a group of loads and distributed generators that work as a single controllable system. The microgrid idea presents the decrease of numerous reverse conversions in an individual AC or DC grid and encourages associations with variable renewable AC and DC sources and loads to power systems. To the customer the microgrid can be designed to meet their special requirements; such as enhancement of local reliability, reduction of feeder losses, local voltages support, increased efficiency using waste heat, correction of voltage sag or uninterruptible power supply. Here photovoltaic system, wind turbine, generator, and battery are utilized for the advancement of the microgrid. Additionally, control systems are actualized for the converters to appropriately facilitate the AC to DC and DC to AC. However, the performance of the optimal fuzzy controller is also justified by comparing with the PI based controller. The outcomes are obtained from the MATLAB/SIMULINK condition. Published under licence by IOP Publishing Ltd.